2012
DOI: 10.1109/tvcg.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Fluids

Abstract: Abstract-We present a fluid simulation method based on Smoothed Particle Hydrodynamics (SPH) in which incompressibility and boundary conditions are enforced using holonomic kinematic constraints on the density. This formulation enables systematic multiphysics integration in which interactions are modeled via similar constraints between the fluid pseudo-particles and impenetrable surfaces of other bodies. These conditions embody Archimede's principle for solids and thus buoyancy results as a direct consequence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 66 publications
(54 reference statements)
0
38
0
Order By: Relevance
“…(24)- (26), and the stabilisation constraint in Eqs. (29)- (31). The Jacobians can be factored to a constant matrix that can be pre-computed, multiplied with current particle displacements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24)- (26), and the stabilisation constraint in Eqs. (29)- (31). The Jacobians can be factored to a constant matrix that can be pre-computed, multiplied with current particle displacements.…”
Section: Discussionmentioning
confidence: 99%
“…This becomes straightforward when the regularisation is introduced by potential energy as quadratic functions in g, i.e. U ε (q) = 1 2 g T ε −1 g. This has been exploited in previous work to constraint-based mod-elling of lumped element beams [29], wires [30], meshfree fluids [31], and granular material [8].…”
Section: Time Discretisationmentioning
confidence: 99%
“…Macklin and Müller [2013] have shown that PBD can be used to simulate fluids. Borrowing the idea of a density estimator from SPH ( [Monaghan 1992;Monaghan 1994]), fluid incompressibility is enforced with a density constraint [Bodin et al 2012]. Position based fluids (PBF) provides another choice for fluid simulation via a particle system.…”
Section: Related Workmentioning
confidence: 99%
“…Maclin and Müller [2013] extended this method to fluid simulation. Following the work by Bodin et al [2012], the density constraint on the i-th particle is defined as follows:…”
Section: Position Based Fluidsmentioning
confidence: 99%
“…The weakly compressible SPH [7] is an advanced method achieving nearly incompressible flow which is a key requirement for practical applications. Later studies such as the predictive-corrective incompressible SPH [8], the constraint fluids [9] and the position based fluids [10] also enforce incompressibility and has been used mainly in computer graphics. The MPS is another approach to accomplish incompressibility with high accuracy and has been successfully applied to a variety of engineering applications.…”
Section: Introductionmentioning
confidence: 99%